Quantitative measurements of reactive oxygen species partitioning in electron transfer flavoenzyme magnetic field sensing - Austvold, Chase K.; Keable, Stephen M.; Procopio, Maria; Usselman, Robert J. (Frontiers in Physiology, 2024)
Biological magnetic field sensing that gives rise to physiological responses is of considerable importance in quantum biology. The radical pair mechanism (RPM) is a fundamental quantum process that can explain some of the observed biological magnetic effects. In magnetically sensitive radical pair (RP) reactions, coherent spin dynamics between singlet and triplet pairs are modulated by weak magnetic fields. The resulting singlet and triplet reaction products lead to distinct biological signaling channels and cellular outcomes. A prevalent RP in biology is between flavin semiquinone and superoxide (O2•-) in the biological activation of molecular oxygen. This RP can result in a partitioning of reactive oxygen species (ROS) products to form either O2•-or hydrogen peroxide (H2O2). Here, we examine magnetic sensing of recombinant human electron transfer flavoenzyme (ETF) reoxidation by selectively measuring O2•-and H2O2 product distributions. ROS partitioning was observed between two static magnetic fields at 20 nT and 50 µT, with a ~13% decrease in H2O2 singlet products and a ~10% increase in O2•- triplet products relative to 50 µT. RPM product yields were calculated for a realistic flavin/superoxide RP across the range of static magnetic fields, in agreement with experimental results. For a triplet born RP, the RPM also predicts about three times more O2 •-than H2O2, with experimental results exhibiting about four time more O2 •-produced by ETF. The method presented here illustrates the potential of a novel magnetic flavoprotein biological sensor that is directly linked to mitochondria bioenergetics and can be used as a target to study cell physiology.